The ovoid amphorae in the Central and Western Mediterranean : between the last two centuries of the Republic and the early days of the Roman Empire - García Vargas, Enrique; García Vargas, Enrique; Almeida, Rui de; Almeida, Rui de; González Cesteros, Horacio; González Cesteros, Horacio; Sáez Romero, Antonio M.; Sáez Romero, Antonio M. (Roman and late antique Mediterranean pottery, 2019)
Based on the proceedings of a workshop held at Seville University in 2015, this book looks at several series of amphorae created in the Late Republican Roman period, sharing a generally ovoid shape in their bodies - a group of material which, until now, has rarely been studied